BHMN PERGURUAN TINGGI, DEAL OR NO DEAL ? - Hidayat, Ach. Syaiful (Jurnal Bestari, 2008)
The government regulation concerning with the management of higher education, stated on UU No.20/2003 which arrange the management of higher education arouses public opinion. Financial matter is the main problem. The regulation mentioned that the government will not give education financial support for the state university particularly for PT BHMN. It means  that, the PT BHMN has not find its educational fund by itself and arrange the activities related to educational system independently.One effect of the implementation of this new paradigm is that the cost of education at state university becomes higher and higher. In fact, the society realizes that to get high education level needs much money. However. it does not mean that all of education cost becomes the responsibility of society. The governments also must be responsible for the education fund. According to UUD 1945 and UUD SISDIKNAS No.20 Tahun 2003, of the government is responsible to give education fund to all of education level:  from elementary level until higher education level. The amount of allocation of the education fund is approximately 20% out  of the government budget.The most important thing is how to increase and develop the quality of education to be better. It is a must in term of education will affect character and personality of the society significantly. In addition, it also contributes to the future of the nation. That is why. PT BHMN management has to pay careful attention to the education quality nor only on education process but also on supplying the education supporting facilities including the lecturer, the quality of education outcome and the quality of students.